„Polska Południa”? Wizerunek Portugalii w "Czterech powstaniach" Karola Hoffmana - Bąk, Magdalena (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2021)
The aim of this article is to analyse the image of Portugal as presented by Karol Hoffman in his book ’Cztery powstania czyli krótki wykład sposobów jakimi dobijały się o niepodległość Grecja, Holandia, Portugalia i Polska’ [Four insurrections that is how Greece, Holland, Portugal, and Poland were fighting for their independence] (1837). Hoffman creates an analogy between the situation of Poland in the partition era and the situation of Portugal when it was united with Spain under the Iberian Union (1580-1640). Comparing Polish efforts with the efforts of the representatives of other European nations,Hoffman tries to revealthe causes ofthe defeat of Poles. However, he has also managed to create an interesting image of the Portuguese that influenced the way the Polish readers regarded this nation in the 19th century.